2019
DOI: 10.1038/s41746-019-0208-8
|View full text |Cite
|
Sign up to set email alerts
|

Desiderata for delivering NLP to accelerate healthcare AI advancement and a Mayo Clinic NLP-as-a-service implementation

Abstract: Data is foundational to high-quality artificial intelligence (AI). Given that a substantial amount of clinically relevant information is embedded in unstructured data, natural language processing (NLP) plays an essential role in extracting valuable information that can benefit decision making, administration reporting, and research. Here, we share several desiderata pertaining to development and usage of NLP systems, derived from two decades of experience implementing clinical NLP at the Mayo Clinic, to inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(59 citation statements)
references
References 30 publications
0
51
0
Order By: Relevance
“…Sign and symptom extraction via natural language processing was accomplished via the MedTagger NLP engine [67] , [68] . The signs and symptoms chosen were selected via a literature review conducted in early March 2020 for known COVID-19 and influenza symptoms [13] , [69] .…”
Section: Methodsmentioning
confidence: 99%
“…Sign and symptom extraction via natural language processing was accomplished via the MedTagger NLP engine [67] , [68] . The signs and symptoms chosen were selected via a literature review conducted in early March 2020 for known COVID-19 and influenza symptoms [13] , [69] .…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, a study conducted by researchers from the University of Alabama found that by applying NLP techniques the reportable cancer cases identified was 22.6% more accurate than a manual review of medical records [47]. Further, various other studies have identified the potential benefits, including effective decision-making by physicians; reducing physician burnout (disillusionment among doctors tired of repetitive data entry tasks and administrative duties as well as excessive time spent combing through patient data); addressing accelerating demand for healthcare services; and dealing with increasing numbers of healthcare claims [48][49][50][51], through the application of NLP techniques in the healthcare context.…”
Section: Nlp In Healthcarementioning
confidence: 99%
“…Table S4 includes the list of symptom categories and the search terms. We then selected relevant clinical note types for each patient, including H&P, Critical Care Notes, Progress Notes, and ED Notes, focusing specifically on the notes created within 48 hours before and after admission. Next, we pre-processed the note text and extracted only the relevant narrative parts, particularly the chief complaint and history of the present illness sections. We then used a COVID-19-customized version of MedTagger, 2 together with our in-house Python tools to (a) identify phrases and synonyms of particular symptoms within the text narratives, (b) determine if these symptom mentions are negated, possible, or positive in their context, (c) classify symptoms into the predefined 11 categories, and (d) map them to their corresponding UMLS Concept Unique Identifiers (CUIs). These NLP pipelines use a combination of machine learning models, including Conditional random fields (CRFs), 3 and contextual rule-based methods, including regular expressions.…”
Section: Natural Language Processingmentioning
confidence: 99%
“…We then used a COVID-19-customized version of MedTagger, 2 together with our in-house Python tools to (a) identify phrases and synonyms of particular symptoms within the text narratives, (b) determine if these symptom mentions are negated, possible, or positive in their context, (c) classify symptoms into the predefined 11 categories, and (d) map them to their corresponding UMLS Concept Unique Identifiers (CUIs). These NLP pipelines use a combination of machine learning models, including Conditional random fields (CRFs), 3 and contextual rule-based methods, including regular expressions.…”
Section: Natural Language Processingmentioning
confidence: 99%